A complex systems perspective on psychedelic brain action. Issue 5 (May 2023) - Girn, Manesh; Rosas, Fernando E.; Daws, Richard E.; Gallen, Courtney L.; Gazzaley, Adam; Carhart-Harris, Robin L.
Highlights: Promising results from clinical trials have ignited a resurgence of scientific interest in serotonergic psychedelic compounds. Functional neuroimaging investigations of acute psychedelic brain action have broadly revealed that they reduce integration within, and segregation between, most large-scale networks. However, spatially specific findings have shown poor convergence. Complex systems approaches characterize the brain as a dynamically evolving system of interacting elements. In doing so, they abstract from localized patterns of activity and instead focus on the dynamical properties of the brain as a whole. Drawing from complexity science, we propose a new 'meta' perspective in which psychedelics are catalysts of a distinct mode of brain functioning that is best characterized by dynamical whole-brain features rather than by region- or network-specific changes. Abstract: Recent findings suggesting the potential transdiagnostic efficacy of psychedelic-assisted therapy have fostered the need to deepen our understanding of psychedelic brain action. Functional neuroimaging investigations have found that psychedelics reduce the functional segregation of large-scale brain networks. However, beyond this general trend, findings have been largely inconsistent. We argue here that a perspective based on complexity science that foregrounds the distributed, interactional, and dynamic nature of brain function may render these inconsistencies intelligible. We propose that psychedelics induce a mode of brain function that is more dynamically flexible, diverse, integrated, and tuned for information sharing, consistent with greater criticality. This 'meta' perspective has the potential to unify past findings and guide intuitions toward compelling mechanistic models.